The impact of sustainability practices to firm performances: evidence from Malaysia / Christopher Jerry Thomas - Thomas, Christopher Jerry (2022)
In line with the UN sustainable development agenda, corporate sustainability practices are critical driver for corporation long-term survival as well as for socio-economic prosperity. Despite the noble ideas, sustainability practices remain neglected in theory, policy, and selectively practice by Malaysian corporations possibly due to unclear evidence on impacts to firm performances. This study aims to provide an empirical analysis on the impact of sustainability practices to firm performance in the context of Malaysia using both aggregate and disaggregated ESG as well as considering impacts to financial and non-financial firm performance. The study employs two sub-samples. First, sub-sample for financial performance consists of 58 public listed firms in Malaysia that have been consistently reporting ESG scores from 2008 to 2019. Second sub-sample for non-financial performance account for 44 listed firms over the period 2013 to 2019. Static unbalanced panel regression is used to analyse the data in annual frequency. The baseline analysis is performed considering linear ESG impacts. While series of robustness models are performed to uncover heterogeneous or non-linear ESG impacts. In addition, interaction analysis is performed to ascertain the role of sustainability governance as moderator to enhance sustainability practices and impacts. In aggregate level, there is a positive relationship between sustainability (ESG) and the firm financial performance measures (ROA, ROE and TQ) through robustness models while brand value reveals that there is no significant relationship with all of the performance variables. In disaggregate level, social (S) score has shown a significant negative relationship with ROE. Interaction analysis indicates that the roles of sustainability governance moderate social (S) score and financial performance (TQ) showing significant positive relationship. The findings provide validation on the positive impacts of firm sustainability practices on financial performance in aggregate level and confirmed the roles of governance in enhancing the positive effects of social indicator to financial performance. This study contributes to the extension of the research framework investigating sustainability practices impacts on firm’s financial and non-financial performances considering both linear and non-linear relationships that provide new insights to inform theory, policy and practice of firm sustainability